Trends in indications and outcomes of liver transplantation in Canada: A multicenter retrospective study. (7th July 2021) - Ivanics, Tommy; Shwaartz, Chaya; Claasen, Marco P. A. W.; Patel, Madhukar S.; Yoon, Peter; Raschzok, Nathanael; Wallace, David; Muaddi, Hala; Murillo Perez, Carla Fiorella; Hansen, Bettina E.; Selzner, Nazia; Sapisochin, Gonzalo
Summary: The liver transplantation (LT) landscape is continuously evolving. We sought to evaluate trends in indications for LT in Canada and the impact of primary liver disease on post‐LT outcomes using a national transplant registry. Adult patients who underwent a primary LT between 2000 and 2018 were retrospectively identified in the Canadian Organ Replacement Registry. Outcomes included post‐LT patient and graft survival. A total of 5, 722 LTs were identified. The number of LT per year increased from 251 in 2000 to 349 in 2018. The proportion of patients transplanted for HCV decreased from 31.5% in 2000 to 3.4% in 2018. In contrast, the percentage of transplants for HCC increased from 2.3% in 2000 to 32.4% in 2018, and those performed for NASH increased from 0.4% in 2005 to 12.6% in 2018. Year of transplant (per 1 year) was protective for both patient (HR:0.96, 95%CI:0.94‐0.97; P < 0.001) and graft survival (HR:0.97, 95%CI: 0.96–0.99; P = 0.001). Post‐LT outcomes have improved over time in this nationwide analysis spanning 18 years. Moreover, trends in the indications for LT have changed, with HCC becoming the leading etiology. The decrease in the proportion of HCV patients and increase in those with NASH has implications on the evolving management of LT patients.